A Phosphine‐ß‐diketiminate Nickel(I)‐Complex for Small Molecule Activation. Issue 12 (14th December 2022) - Zovko, Christina; Krätschmer, Frederic; Schmidt, Sarah; Seifert, Tim P.; Gamer, Michael T.; Roesky, Peter W.
Abstract: A bis(diphenyl)‐phosphine functionalized ß‐diketimine ligand (PNac‐H) was applied for the synthesis of a subvalent Ni(I) complex [PNac‐Ni]. Here, the Ni(I) center is stabilized by a tetradentate PNNP‐type pocket, forming a square planar coordination sphere. Subsequently, the Ni(I) complex was investigated with regard to its reactivity and the activation of small molecules. The reductive potential of Ni(I) enabled an activation of different substrate classes, such as CH2 X2 (X=Br, I), I2 or Ph2 E2 (E=S, Se). The ligand's design allows a stabilization of the reactive Ni(I) species while at the same time enabling activation processes due to a hemilabile coordination behavior and accessible axial coordination sites. The activation products have been characterized by single crystal X‐ray diffraction, NMR and IR spectroscopy as well as elemental analysis. Abstract : A phosphine‐ß‐diketiminate Ni(I)‐complex uses the reductive potential of Ni(I) to enable the activation of small molecules with different substrate classes, such as CH2 X2 (X=Br, I), I2 or Ph2 E2 (E=S, Se). The ligand's design allows a stabilization of the reactive Ni(I) species while at the same time enabling activation processes due to a hemilabile coordination behavior.